Detection and characterization of respiratory viruses causing acute respiratory illness and asthma exacerbation in children during three different seasons (2011–2014) in Mexico City. Issue 6 (November 2015) - Moreno‐Valencia, Yazmin; Hernandez‐Hernandez, Victor A.; Romero‐Espinoza, Jose A. I.; Coronel‐Tellez, Rodrigo H.; Castillejos‐Lopez, Manuel; Hernandez, Andres; Perez‐Padilla, Rogelio; Alejandre‐Garcia, Alejandro; de la Rosa‐Zamboni, Daniela; Ormsby, Christopher E.; Vazquez‐Perez, Joel A.
<x xml:space="preserve">Abstract</x> Background Viral infections play a significant role in causing acute respiratory infections (ARIs) and exacerbations of chronic diseases. Acute respiratory infections are now the leading cause of mortality in children worldwide, especially in developing countries. Recently, human rhinovirus (HRV) infection has been emerged as an important cause of pneumonia and asthma exacerbation. Objectives To determine the role of several viral agents principally, respiratory syncytial virus, and HRV in children with ARIs and their relationship with asthma exacerbation and pneumonia. Methods Between October 2011 and March 2014, 432 nasopharyngeal samples of children <15 years of age with ARI hospitalized at a referral hospital for respiratory diseases were tested for the presence of respiratory viruses using a multiplex RT‐qPCR. Clinical, epidemiological, and demographic data were collected and associated with symptomatology and viral infections. Results Viral infections were detected in at least 59·7% of the enrolled patients, with HRV (26·6%) being the most frequently detected. HRV infections were associated with clinical features of asthma and difficulty in breathing such as wheezing (P = 0·0003), supraesternal (P = 0·046), and xiphoid retraction (P = 0·030). HRV subtype C (HRV‐C) infections were associated with asthma (P = 0·02). Conclusions Human rhinovirus was the virus most commonly detected in pediatric patients with ARI. There is also an association of HRV‐C infection with asthma exacerbation, emphasizing the relevance of this virus in severe pediatric respiratory disease.